Human rights in the new eco-social contract: Exploring a just transition through public services and social security - Sylvain Aubry; Matt McConnell; Sarah Saadoun; Lena Simet (United Nations Research Institute for Social Development (UNRISD), 2024)
To address the current multiple crises that are sometimes referred to as leading to "a breakdown" of current social contracts, civil society, academics and international institutions have been proposing a range of ideas for societal transformation, from "human rights economy" to "just transition." Among these, the idea of a new eco-social contract has gained particular traction and could help bring together a number of the proposals for change. However, the content of such new eco-social contracts needs to be fleshed out. This paper proposes an initial exploration of whether, and if so, how, human rights can help provide guidance to the understanding of new eco-social contracts. To do so, this paper focuses on one of the three pillars identified by UNRISD to build new ecosocial contracts: transformative social policies. It reviews the main human rights norms and obligations with respect to two of the policy areas under this pillar-universal quality public services and the right to social security-and explores how these can be applied in the context of removing fossil fuel subsidies as an illustrative case study for incorporating human rights into shifting social contracts. On this basis, the paper makes four preliminary reflections on the relationship between human rights and new eco-social contracts. Firstly, if momentum toward new eco-social contracts presents an opportunity for a renewed approach to the realization of human rights, the human rights community should take it into account in its approach to interpret and develop rights. Secondly, the human rights framework, if used and interpreted adequately (importantly, taking into account analysis from other fields), has the potential to guide social contracts to avoid reproducing or creating new unequal power dynamics and abuses. Thirdly, human rights could provide a framework from which to build the consensus that new eco-social contracts require, which can be particularly challenging when it requires a redistribution of resources. Fourthly, human rights could play a role in assessing these contracts and provide a well-established framework through which to identify ecosocial contracts that advance social justice and distinguish them from social contracts that do not meet this normative objective.
Keywords: 330